Advanced Nanoscale ULSI Interconnects: Fundamentals and Applications - Shacham-Diamand, Yosi.; Osaka, Tetsuya; Datta, Madhav; Ohba, Takayuki; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Advanced Nanoscale ULSI Interconnects: Fundamental and Applications brings a comprehensive description of copper based interconnect technology for Ultra Large Scale Integration (ULSI) technology to Integrated Circuit (ICs) application. This book reviews the basic technologies used today for the copper metallization of ULSI applications: deposition and planarization. It describes the materials used, their properties, and the way they are all integrated, specifically in regard to the copper integration processes and electrochemical processes in the nanoscale regime. The book also presents various novel nanoscale technologies that will link modern nanoscale electronics to future nanoscale based systems. This diverse, multidisciplinary volume will appeal to process engineers in the microelectronics industry; universities with programs in ULSI design, microelectronics, MEMS and nanoelectronics; and professionals in the electrochemical industry working with materials, plating and tool vendors.
Challenges in ULSI Interconnects - Introduction to the Book -- Technology Background -- MOS Device and Interconnects Scaling Physics -- Interconnects in ULSI Systems: Cu Interconnects Electrical Performance -- Electrodeposition -- Electrophoretic Deposition -- Wafer-Level 3D Integration for ULSI Interconnects -- Interconnect Materials -- Diffusion Barriers for Ultra-Large-Scale Integrated Copper Metallization -- Silicides -- Materials for ULSI metallization - Overview of Electrical Properties -- Low-? Materials and Development Trends -- Electrical and Mechanical Characteristics of Air-Bridge Cu Interconnects -- ALD Seed Layers for Plating and Electroless Plating -- Deposition Processes for ULSI Interconnects -- Electrochemical Processes for ULSI Interconnects -- Atomic Layer Deposition (ALD) Processes for ULSI Manufacturing -- Electroless Deposition Approaching the Molecular Scale -- Modeling -- Modeling Superconformal Electrodeposition Using an Open Source PDE Solver -- Electrochemical Process Integration -- to Electrochemical Process Integration for Cu Interconnects -- Damascene Concept and Process Steps -- Advanced BEOL Technology Overview -- Lithography for Cu Damascene Fabrication -- Physical Vapor Deposition Barriers for Cu metallization - PVD Barriers -- Low-k Dielectrics -- CMP for Cu Processing -- Electrochemical View of Copper Chemical-Mechanical Polishing (CMP) -- Copper Post-CMP Cleaning -- Electrochemical Processes and Tools -- Electrochemical Processing Tools for Advanced Copper Interconnects: An Introduction -- Electrochemical Deposition Processes and Tools -- Electroless Deposition Processes and Tools -- Tools for Monitoring and Control of Bath Components -- Processes and Tools for Co Alloy Capping -- Advanced Planarization Techniques -- Metrology -- Integrated Metrology (IM) History at a Glance -- Thin Film Metrology - X-ray Methods -- Summary and Foresight -- Emerging Nanoscale Interconnect Processing Technologies: Fundamental and Practice -- Self-Assembly of Short Aromatic Peptides: From Amyloid Fibril Formation to Nanotechnology.
Keywords: Chemistry; Electrochemistry; Chemical engineering; Electrical engineering; Materials science; Nanotechnology; Chemistry; Electrochemistry; Materials Science, general; Industrial Chemistry/Chemical Engineering; Electrical Engineering; Nanotechnology; Electronic books